A study of the type material of Lithophyllum hibernicum (Lithophyllaceae, Corallinales, Rhodophyta) with comments on L. bathyporum and L. incrustans. Issue 1 (2nd January 2020) - Athanasiadis, Athanasios
ABSTRACT: The original material of Lithophyllum hibernicum Foslie was re-examined and two different species, unequally represented in the collection were found: most thalli belong to a sterile species of Lithophyllum, represented in the protologue by elements related to cell size and coaxial arrangement. A few sterile thalli belong to Lithothamnion cf. corallioides, and this species is also represented in the protologue by a single statement of branch size. Yet, the species of Lithophyllum is the sole representative in Foslie's unpublished materials included in the type collection in TRH. A previous lectotypification, contradicting Art. 9.14 (that demands the type to correspond to its original description rather than to a certain taxonomic concept), is sustained because it preserves Foslie's intent. The lectotype of L . hibernicum is a sterile, branched rhodolith with characteristic cup- or funnel-shaped formations on its thallus. Syntypes are inhabited by an endo-, epiphytic species of Gelidiales forming openings resembling conceptacle ostioles. Molecular comparison with topotypes is needed before synonymy with the common epilithic species Lithophyllum bathyporum in the NE Atlantic should be accepted.